Grammar is wonderful: the case of the complex sentence in Italian in the teaching of Italian as a foreign language. Between grammar instruction and cognitive linguistics - Kwapisz-Osadnik, Katarzyna (Kwartalnik Neofilologiczny, 2026)
This study examines the formal and functional classification of subordinate clauses as a basis for a cognitively oriented approach to teaching Italian syntax. It compares syntactic models in Italian and Polish grammar manuals, highlighting potential cross-linguistic influences. Drawing on cognitive linguistics, the paper proposes alternative strategies that treat syntax as a cognitive tool for organizing and expressing thought. Key aims include linking clause structure to the cognitive process of construal and exploring ways to simplify the classification of subordinate clauses.